THE EFFECT OF ROOT STIMULANT ON ECTOMYCORRHIZAL COLONIZATION OF GNETUM SEEDLINGS (Gnetum gnemon L.) - Arum Sekar Wulandari; Rizki Adisetia (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Ectomycorrhizal fungi usually infect the young lateral roots. Root stimulant can induce the growth of new lateral roots after application of root pruning. This research is aimed at determining the exact amount of root stimulant concentration that suffices the condition of increased root colonization of gnetum seedling by mycorrhizal fungi. The research were tested in a greenhouse in a completely randomized design for 8 months. Four levels of root stimulant concentation was used, i.e. 0.00%, 1.00%, 1.25% and 1.67%. All treatments were treated with root pruning and ectomycorrhizal fungi (Scleroderma spp.) inoculation. Growth parameters observed were the number of new roots, the percentage of ectomycorrhizal colonization, diameter, height, shoot wet biomass, shoot dry biomass, root wet biomass, and root dry biomass. The results showed that all the roots of Gnetum seedlings infected by Scleroderma spp. Root stimulant had significant effects on increasing the growth of new roots. Root stimulant with concentration 1.67% gave the best growth response on all parameters except root dry biomass. The number of new roots was 35.50, the percentage of ectomycorrhizal colonization 58.47%, diameter 3.57 mm, height 48.21 cm, shoot wet biomass 8.57 g, shoot dry biomass 3.56 g, and root wet biomass 5.81 g.Key words: Gnetum gnemon, mycorrhizal colonization, plant growth, root stimulant, Scleroderma